The Application of Self-Management Techniques within Individual Counseling to Reduce Academic Procrastination among High School Students - Agussalim, Agussalim; Hikmah, Muh. Syawal; Kaffah, Muhammad Silmi (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to describe the academic procrastination behavior of students at SMA Negeri 26 Bone and evaluate the Self-Management technique's effectiveness in reducing such behavior. The study uses a quantitative approach with a Single Subject Research (SSR) method and an A-B-A design. The subjects were two second-year students with high levels of academic procrastination. Data were collected through observations and interviews and then analyzed descriptively and visually. The results show that the subjects' academic procrastination was high before the intervention. After applying the Self-Management technique, there was a significant decrease in their procrastination behavior. In conclusion, the Self-Management technique effectively reduces academic procrastination among students at SMA Negeri 26 Bone. The implications of this study provide a basis for teachers and counselors to implement Self-Management techniques as an intervention strategy to improve students' learning discipline and academic achievement.